EVALUATION OF FREE RADICAL SCAVENGING ACTIVITY OF ERYTHRINA INDICA LEAVES - RUPESH PINGALE,; GOURI KUMAR DASH, (International Journal of Pharma and Bio Sciences, 2016)
The antioxidant activity of methanol extract of the leaves of Erythrina indica was evaluated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and Hydrogen peroxide scavenging assay methods. Ascorbic acid was used as a reference standard. The extract revealed significant activities in both antioxidant assays compared to the reference standard in a concentration dependent manner.The results suggest that the antioxidant properties of the extract may be due to the presence of flavonoids and related polyphenolic compounds, as reported in previously published literatures.